Between celebrity and glory? Textual after-image in late eighteenth-century France - Goodman, J (Routledge, 2016)
Eighteenth-century France had a particular interest in identifying and celebrating its ‘great men’, the model individuals through whom it defined its national identity. Across the century, authors, statesmen, scientists and artists were celebrated by the state, in a cult of glory that culminated in the creation of the secular temple of the Panthéon in 1791. Yet the eighteenth century is also acknowledged as the starting point of a very different sort of recognition: the widespread curiosity about a public figure’s private life that lies at the heart of modern celebrity culture. Rousseau and Voltaire incarnated these two burgeoning forms of fame. This article examines the literary discourse that surrounded their deaths in 1778 and their later inclusion in the Panthéon, analysing the use that was made of their textual remains and considering how their glorious posthumous status related to their public image in life. Using these case studies, I suggest that authors occupy a privileged place in the conversion of lifetime celebrity into enduring posthumous fame; not only – as has traditionally been argued – thanks to the durability of the text, but also because of its flexibility and a created intimacy that mimics the process by which literary celebrity is created in life.